Effective science communication: a practical guide to surviving as a scientist - Illingworth, Sam (IOP ebooks, 2020)
Being a scientist in the 21st century can be extremely demanding. In addition to conducting exceptional research we are expected to communicate it effectively to a variety of audiences, from scientists and students to policymakers and press officers. This book provides a roadmap for how to disseminate your research findings in an engaging manner via a range of channels, such as scientific publications, press releases, social media and outreach. Furthermore, by providing advice and worked examples on how to fund and publish your research, develop additional skills and support inclusive practices, this book provides a comprehensive handbook for how to be a successful scientist. This second edition brings the text up to date and includes additional material, while retaining the combination of clear insight and practical advice that made the first edition essential.